Pengaruh inflasi dan capital inflow terhadap nilai tukar: Studi kasus Indonesia-Malaysia - Nindi Listika; Imam Asngari; Suhel Suhel (Jurnal Ekonomi Pembangunan, 2018)
This study aims to determine how the effects of inflation and capital inflow on the rupiah and ringgit on the US dollar (a comparative study: Indonesia-Malaysia). The data used in this research is secondary data of world development indicators and Bank Indonesia. The analysis technique used in this research is quantitative analysis techniques with multiple linear regression method. The results of this study indicate that inflation Indonesia and Malaysia affect the rupiah and ringgit negatively while the variable capital inflow Indonesia and Malaysia affect the rupiah and ringgit positively significant.